2013
DOI: 10.11607/jomi.2719
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Evaluation of Alterations of the Buccolingual Width of the Alveolar Ridge After Immediate Implant Placement Associated with the Use of a Synthetic Bone Substitute

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…, Assaf et al. ), or utilizing different definition of the dimensional change(Koh et al. ) were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…, Assaf et al. ), or utilizing different definition of the dimensional change(Koh et al. ) were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…When analysing bone dimensional changes three methods have been employed: clinical intrasurgical measurements by means of a re-entry procedure (Gher et al 1994;Boticelli et al 2004Boticelli et al , 2008Chen et al 2007;Ferrus et al 2010) or radiographic measurements on CBCTs (Roe et al 2012;Benic et al 2012;Degidi et al 2012;Assaf et al 2013;Morimoto et al 2015) or periapical radiographs Valentini et al 2010;Cosyn et al 2013;Covani et al 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Immediate implant placement does not prevent loss of alveolar dimensions 1,10‐12 and, for that reason, alternative treatment approaches to preserve alveolar dimensions during immediate implant placement have been investigated 13 , 14 …”
mentioning
confidence: 99%
“…Use of biomaterials in the gap between implant and buccal bone wall aims to minimize bone resorption at the implant site 13 . Several studies have reported lower resorption of buccal bone walls when using biomaterials 14–17 . Such studies have evaluated extraction sockets and immediate implants at sites with intact bone walls, but little is known with regard to sockets that feature buccal bone loss.…”
mentioning
confidence: 99%